UPAYA PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PENATAAN TENAGA HONORER TAHUN 2023 - Prayoga, Rendi Rikki; Tinov, M.Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research is motivated by the large number of honorary workers in government agencies, which affects the quality of honorary workers in government, therefore based on the law. No. 48 of 2005 which has been changed to PP. No. 56 of 2012 concerning the Appointment of Honorary Personnel to Become Civil Servants, the government is making efforts to reorganize honorary personnel who have contributed to the government, namely by appointing them to become Civil Servants. The aim of this research is to determine the efforts of the Meranti Islands Regency government and the obstacles in the 2023 Regional Honorary Workforce Arrangement. The type of research in writing this thesis is descriptive qualitative, where this research explores and analyzes to provide meaning and significance in solving problems. This writing consists of primary data, namely research in the form of interviews, documentation and observations and secondary data obtained, namely the results of interviews in research on the implementation of the Meranti Islands Regency Regional Government Policy in the Arrangement of Regional Honorary Personnel in 2023. The results of the Meranti Islands Regency Regional Government Policy Research in Arranging Regional Honorary Personnel in 2023 are that the Government has made several efforts in structuring honorary personnel in Meranti Islands Regency Government agencies so that the Honorary Workforce is more optimal. The existence of such a large number of honorary personnel is certainly not in line with Government Regulation No. 49 of the Year 2018 Article 96 concerning management of government employees with work agreements. Keywords: Regional Government Policy, Arrangement of Honorary Personnel